TOPOS: A new topometric patient positioning and tracking system for radiation therapy based on structured white light. Issue 4 (29th March 2013) - Lindl, Bastian L.; Müller, Reinhold G.; Lang, Stephanie; Herraiz Lablanca, Maria D.; Klöck, Stephan
Abstract : Purpose: : A patient positioning system for radiation therapy based on structured white light and using off‐the‐shelf hardware components for flexibility and cost‐effectiveness has been developed in house. Increased accuracy, patient comfort, abandonment of any skin marks, accelerated workflow, objective reading/recording, better usability and robust sensor design, compared to other positioning approaches, were the main goals of this work. Another aim was the application of a 6 degrees of freedom tracking system working without dose deposition. Methods: : Two optical sensors are the main parts of the TOPOS® system (To pometricalPos itioning, cyberTECHNOLOGIES, Germany). The components: cameras, projectors, and computers are commercial off‐the‐shelf products, allowing for low production costs. The black/white cameras of the prototype are capable of taking up to 240 frames per second (resolution: 640 × 488 pixels). The projector has a resolution of 1024 × 768 and a refresh rate of 120 Hz. The patient's body surface is measured continuously and registered to a reference surface, providing a transformation to superimpose the patient's surface to the reference (planning CT) surface as best as possible. The execution of the calculated transformation provides the correct patient position before the treatment starts. Due to the high‐speed acquisition of the surfaces, a surveillance of the patient's (respiration) motion during treatment is also accomplished. The accuracy of the system was determined using a male mannequin. Two treatment sites were evaluated: one simulating a head and neck treatment and the other simulating a thoracic wall treatment. The mannequin was moved to predefined positions, and shift vectors given by the surface registration were evaluated. Additionally manual positioning using a color‐coding system was evaluated. Results: : Two prototypes have been developed, each allowing a continuous high density scan of a 500 × 500 × 400 mm 3 (L × W × D) large volume with a refresh rate of 10 Hz (extendible to 20 Hz for a single sensor system). Surface and position correction display, as well as respiratory motion, is shown in real‐time (delay < 200 ms) using present graphical hardware acceleration. For an intuitive view of the patient's misalignment, a fast surface registration algorithm has been developed and tested and a real‐time color‐coding technique is proposed and verified that allows the user to easily verify the position of the patient. Using first the surface registration and then the color coding the best results were obtained: for the head and neck case, the mean difference between the actual zero position and the final match was 0.1 ± 0.4, −0.2 ± 0.7, and −0.1 ± 0.3 mm in vertical, longitudinal, and lateral direction. For the thoracic case, the mean differences were 0.3 ± 0.5, −0.6 ± 1.9, 0.0 ± 0.4 mm. Conclusions: : The presented system copes with the increasing demand for more accurate patient positioning due to more precise irradiation technologies and minimizes the preparation times for correct patient alignment, therefore optimizing the treatment workflow. Moreover, TOPOS is a versatile and cost effective image guided radiation therapy device. It allows an objective rating of the patient's position before and during the irradiation and could also be used for respiratory gating or tracking.